Reaching Diverse Participants Utilizing a Diverse Delivery Infrastructure: A Replication Study - Smith, Matthew Lee; Ory, Marcia G.; Ahn, SangNam; Belza, Basia; Mingo, Chivon A.; Towne, Samuel D.; Altpeter, Mary (Frontiers in Public Health, 2015)
This replication study examines participant recruitment and program adoption aspects of disease self-management programs by delivery site types. Data were analyzed from 58,526 adults collected during a national dissemination of the Stanford suite of Chronic Disease Self-Management Education (CDSME) programs spanning 45 states, the District of Columbia, and Puerto Rico. Participant data were analyzed using multinomial logistic regression to generate profiles by delivery site type. Profiles were created for the five leading delivery site types, which included senior centers or Area Agencies on Aging (AAA), residential facilities, healthcare organizations, community or multi-purpose centers, and faith-based organizations. Significant variation in neighborhood characteristics (e.g., rurality, median household income, percent of the population age 65 years and older, percent of the population that is non-Hispanic white) and participant characteristics (e.g., age, sex, ethnicity, race, rurality) were observed by delivery site type. Study findings confirm that these evidence-based programs are capable of reaching large numbers of diverse participants through the aging services network. Given the importance of participant reach and program adoption to the success of translational research dissemination initiatives, these findings can assist program deliverers to create strategic plans to engage community partners to diversify their participant base.